1994
DOI: 10.1017/s0022336000026317
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic development of Pa element cup microsculpture in Lochriea commutata (Branson and Mehl, 1941) (Conodonta, Carboniferous): taxonomic implications

Abstract: Cup nodes on Lochriea commutata Pa elements bear microsculpture fields composed of polygonal microsculpture. As Pa elements grow larger, the cup nodes and their microsculpture fields increase in size during early to middle growth. With subsequent growth, cup nodes may broaden transversely, split, fuse, or cease to broaden; similarly, their microsculpture fields may increase in size, split, or disappear as the element gets larger. The loss of microsculpture fields results in the loss of polygonal microsculpture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(25 citation statements)
references
References 4 publications
2
23
0
Order By: Relevance
“…by the circum stance that the P and S elements with one costa on each side have not striations" (Zhang, 1998, p. 17). As noted in this paper's discussion of Staufferella polonica (Spassov and Teller, 1963), the use of microornamentation to diagnose genera may be problem atic (see von Bitter and Norby, 1994). I follow the suggestion that is illustrated in Dzik's (1983) figure 4 in referring A. semisym metricus to Besselodus.…”
Section: Oslodus Semisymmetricusmentioning
confidence: 81%
See 1 more Smart Citation
“…by the circum stance that the P and S elements with one costa on each side have not striations" (Zhang, 1998, p. 17). As noted in this paper's discussion of Staufferella polonica (Spassov and Teller, 1963), the use of microornamentation to diagnose genera may be problem atic (see von Bitter and Norby, 1994). I follow the suggestion that is illustrated in Dzik's (1983) figure 4 in referring A. semisym metricus to Besselodus.…”
Section: Oslodus Semisymmetricusmentioning
confidence: 81%
“…Differences in microornamentation may not be good criteria to diagnose Staufferella from Scolopodus. In a somewhat analogous situation, von Bitter and Norby (1994) concluded that the microsculpture on the Caboniferous genus Lochriea should not be used to distinguish spe cies of this genus because the microsculpture changes during on togeny.…”
Section: Distacodus! Falcatus Stauffermentioning
confidence: 99%
“…in some growth series of Lochrieu commututu Pa elements (Fig. 6A), there is a correlation between the loss of polygonal microsculpture on the cup nodes of the largest elements (von Bitter & Norby 1994) and the presence of only 'wispy' scattered white matterlacunate spaces interconnected by irregular radiatingtubules in cusps and denticles (Sansom et ul 1992). Conversely, the cup nodes of the largest elements (von Bitter & Norby 1994) of other growth series retain polygonal microsculpture and show abundant, solid-appearing white matter (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…commutata according to priority and availability. First and foremost, that conclusion is based on our detailed comparison and documentation (von Bitter and Norby, 1994a; Fig. 3) of the overall morphology of P 1 elements in the type specimens of L .…”
Section: Taxonomic Notesmentioning
confidence: 88%
“…commutata apparatus and noted the general agreement regarding the apparatus composition of the genus. Krumhardt et al (1996) supported the use of Lochriea and documented the gradual acceptance of the genus by numerous workers since 1986, including Armstrong and Purnell (1987), Grayson (1990), Ramovš (1990a, b), Rexroad and Horowitz (1990), Whiteside and Grayson (1990), Weibel and Norby (1992), Kolar-Jurkόvsek and Jurkόvsek (1993), Nemirovskaya et al (1994), and von Bitter and Norby (1994a, b). We add Purnell (1992) and Varker (1994) to this list, but make no claim that the citations before or after 1996 are either exhaustive or complete.…”
Section: Taxonomic Journey Of Lochriea Scott 1942mentioning
confidence: 99%